5m(m-2)-(m+2)(m-3) решите

0 голосов
291 просмотров

5m(m-2)-(m+2)(m-3) решите


Алгебра (24 баллов) | 291 просмотров
Дано ответов: 2
0 голосов
Правильный ответ

5m(m-2)-(m+2)(m-3)=
=5m^2-10m-(m^2+2m-3m-6)=
=5m^2-10m-m^2-2m+3m+6=
=4m^2-9m+6
  


       0,125^6 × 8^6
 = 1^12=1

(510 баллов)
0

0,125^6 × 8^6 = 1^12=1

0

спсибо

0

спасибо*

0

пожалуйчта)))

0

пожауйста)

0

3^5*3^6

0

--------

0

(3^3)^3

0

это дробью

0

3^9

0 голосов

Вот упрощение:
4m^2-9m+6

(20 баллов)
0

спасибо

0

решите вот это :

0

0.125^6*8^6

0

что решить?

0

надо еще что то решить?